도로시설물의 전과정 탄소배출량 산정을 위한 시공단계 탄소배출원단위 구축 - 곽인호(In Ho Kwak); 김건호(Kun Ho Kim); 조우형(Woo Hyoung Cho); 박광호(Kwang Ho Park); 황용우(Young Woo Hwang) (Daehan hwan'gyeong gonghag hoeji, 2015)
Carbon emissions in construction stage is very high because lots of construction machines and materials are required to be used at a road construction stage. Many researcher carried out application of carbon emissions estimation methodology during the life cycle of road infrastructure in order to reduce greenhouse gas emissions in the road sector. But the calculation of carbon emissions is difficult because data collection is difficult and calculation procedure is complex. In this study, a basic unit of carbon emissions in construction stage of the road infrastructure was developed in order to get the quantitative determination of carbon that occurs. Carbon emissions of the expressway and common state road was calculated by using the basic unit of carbon emissions and application plan of basic unit of carbon emissions are presented. 도로는 건설 시 많은 건설자재와 장비를 사용하여 시공단계에서의 탄소배출량이 매우 높다. 도로분야에서의 온실가스 감축을 위하여 도로의 전과정에 걸친 탄소배출량 산정 방법에 대한 연구를 수행하여 탄소배출량 산정방법을 정립하였으나, 수집해야 하는 자료 확보와 산정 절차가 복잡해 탄소배출량 산정에 어려움을 겪고 있다. 이에 따라 본 연구에서는 도로시설 물의 시공단계에서 발생하는 탄소의 정량적 산정을 쉽게 할 수 있도록 탄소배출원단위를 개발하여 제시하고, 이를 활용하여 2012년 기준으로 고속국도 및 일반국도의 탄소배출량을 정량적으로 산정 후 활용방안을 제시하였다.